Supply Chain Management Efficiency in Logistics Companies in Indonesia: a Digital Approach - Amelia Hayati (PT. Anagata Sembagi Education, 2025)
Digitalization has become a crucial element in improving the efficiency of Supply Chain Management (SCM) in Indonesia. This study aims to analyze the impact of digitalization on operational efficiency in SCM across several companies in Indonesia. The method used is a quantitative approach with data collection through surveys to companies that have implemented digital technologies in their supply chains. The data were analyzed using descriptive statistics and regression. The results indicate that digitalization positively impacts reducing operational costs, increasing delivery speed, and improving the accuracy of inventory management and forecasting. The use of technologies such as IoT, big data, and cloud computing has significantly enhanced SCM efficiency. However, challenges such as high implementation costs and limited technological infrastructure remain major obstacles. This study concludes that digitalization can improve SCM efficiency, but attention must be paid to factors influencing the successful implementation of digital technologies.